(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
Middle school social studies explores how people, past and present, live together. Oftentimes, teachers accentuate recall of historical facts rather than relationships between humans. Requiring recall over reflection on how people lived through historical events can result in disengaged students. One solution to address the lack of student interest is for teachers to use multiple modes of delivery through triangular texts (tri-texts). This paper provides educators with strategies to insert tri-texts into their curriculum through story, art, poetry, video, and song. These methods complement the textbook to improve the depth and breadth of knowledge about historical events to create benefits for students, including a more rigorous curriculum, higher visual literacy skills, and increased critical thinking combined with interest and curiosity.